DEFECTS IN THE WRITTEN SPEECH OF ELEMENTARY SCHOOL STUDENTS WITH INTELLECTUAL DISABILITIES AND THEIR ELIMINATION (Conference Zone, 2022)
Effective education and upbringing of children with developmental disabilities, its development opportunities and features to create social adaptation it depends on being able to evaluate it correctly. This kata requires skill. This article is about the problems in written speech of children with developmental disabilities.